2015 10th International Conference on Information, Communications and Signal Processing (ICICS) 2015
DOI: 10.1109/icics.2015.7459882
|View full text |Cite
|
Sign up to set email alerts
|

Resolving focal plane ambiguity in depth map creation from defocus blur using chromatic aberration

Abstract: Focal plane ambiguity in depth map creation from defocus blur has remained an challenging problem. In this paper, we present a method to resolve this issue with the help of Chromatic Aberration(CA). CA is a distortion referred to focal length variation of the lens with wavelength of light. When light, a mixture of various monochromatic components, passes through a lens, multiple focal planes are generated due to CA. There also exists an inherent ordering in the defocus blur of the object for different RGB comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Negative value of k1 is not possible and denotes serious errors in estimation process. These two types of focusing condition give rise to Focal Plane Ambiguity and can be removed using method such as [57, 58]. Generally, images of the scene with focus at nearest object are taken for full defocus map quality evaluation.…”
Section: Applications Of Bplcmentioning
confidence: 99%
“…Negative value of k1 is not possible and denotes serious errors in estimation process. These two types of focusing condition give rise to Focal Plane Ambiguity and can be removed using method such as [57, 58]. Generally, images of the scene with focus at nearest object are taken for full defocus map quality evaluation.…”
Section: Applications Of Bplcmentioning
confidence: 99%
“…The focal plane ambiguity results from the fact that DfD from a single image cannot differentiate on which side of the focal plane the objects are placed [8]. Kumar et al [16] demonstrated that chromatic aberration provides an effective indicator to solve the focal plane ambiguity. Second, the motion blur influences the defocus estimation.…”
Section: Related Workmentioning
confidence: 99%
“…First, objects placed in front and behind the focal plane may be viewed with exactly the same amount of defocus blur [23]. Kumar et al [24] used the chromatic aberration as a clue to solve the focal plane ambiguity. Second, in dynamic scenes both depth and motion contribute to the blur.…”
Section: B Depth From Defocusmentioning
confidence: 99%
“…Manuscript received: September, 9, 2017; Accepted October, 24,2017 We begin with ORB-SLAM [1], which is one of the best monocular SLAM systems currently available. This system uses ORB features to represent the environment and select a set of frames (keyframes) for representing the camera poses.…”
Section: Introductionmentioning
confidence: 99%